Indonesia : CPSS-IOSCO Recommendations for Securities Settlement Systems: The Equity and Corporate Bonds Securities Settlement Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses findings of the joint IMF-World Bank Indonesia Financial Sector Assessment Program (FSAP) undertaken during 2009- 10. The assessment was conducted on processes and functions, as opposed to institutions and with the cooperation of the Bapepam-LK, the Bank Indonesia. It was found that the legal framework governing the clearing and settlement operations of the equity and corporate bond market supports some, but not all, of the key elements of the clearing and settlement process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet